Gel‐based separation of phosphoproteins in samples stored in urea/thiourea after precipitation by lanthanum chloride. Issue 4 (18th February 2013) - Pink, Mario; Stein, Christine; Verma, Nisha; Rettenmeier, Albert W.; Schmitz‐Spanke, Simone
<x xml:space="preserve">Abstract</x> The recent introduction of the La3+ precipitation method for the enrichment of phosphoproteins allows a gel‐based analysis of these posttranslationally modified proteins. However, if this method is applied to cell lysates stored in urea‐containing lysis buffer for an extended period of time, incomplete phosphoprotein recovery is observed. We ascribe this effect to the presence of urea in the lysis buffer. To overcome this problem various strategies were tested, where cell lysates stored at least for one year were utilized. By applying an optimized protocol approximately 250 proteins could be observed following separation by 2DE.